Considerations on interdiscipline and multidiscipline with regard to palliative care - Ferraro, Juan Manuel (Alternativas, 2021)
We present some reflections when naming a set of diverse professionals working in Palliative Care. This issue led us to question interdiscipline and multidiscipline, in order to consider which of these two concepts is more coherent and allowed us to better define the practice. The analysis led us to note the conceptual confusion in the definition of these terms, a situation which also leads to the indiscriminate use of one or the other by professionals. Choosing to consider both as terms that refer to different issues and ways of working, and noting the specificity of the work in this particular field of Palliative Care –due to its inherent multidimensionality–, interdiscipline is taken as the definition that describes and guides the practice, and which aims to produce a care work. The question then remains as to by whom this production is carried out: by an Interdisciplinary Palliative Care Unit, or by a Team? From the proposed development, considering that interdiscipline is based on heterogeneity, and that this is lost in the homogeneity of the indiscriminate Unit, it is concluded that the term that best applies to our case is that of Team. Our development concludes by proposing a question: can Palliative Care work be done in any other way than interdisciplinary?.